# SOLUTION: A father is 30 years older than his son however he will be only thrice as old as the son after 5 years what is father's present age ? (a) 40 yrs (b) 30 yrs (c) 50 yrs

Algebra ->  Algebra  -> Customizable Word Problem Solvers  -> Age -> SOLUTION: A father is 30 years older than his son however he will be only thrice as old as the son after 5 years what is father's present age ? (a) 40 yrs (b) 30 yrs (c) 50 yrs       Log On

 Ad: Over 600 Algebra Word Problems at edhelper.com Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Word Problems: Age Solvers Lessons Answers archive Quiz In Depth

 Click here to see ALL problems on Age Word Problems Question 262682: A father is 30 years older than his son however he will be only thrice as old as the son after 5 years what is father's present age ? (a) 40 yrs (b) 30 yrs (c) 50 yrs (d) none of these Found 2 solutions by palanisamy, Theo:Answer by palanisamy(496)   (Show Source): You can put this solution on YOUR website!Let the age of the son = x Then the age of his father = x+30 Given,father will be only thrice as old as the son after 5 years x+30+5 = 3(x+5) x+35 = 3x+15 35-15 = 3x-x 20 = 2x 2x = 20 x = 20/2 = 10 Therefore the age of his father = x+30 = 10+30 = 45 years Answer by Theo(3504)   (Show Source): You can put this solution on YOUR website!f = father's age. s = son's age. the father is 30 years older than his son. f = s + 30 in 5 years, the father will be 3 times as old as his son. f + 5 = 3 * (s+5) what is the father's age? solve these 2 equations simultaneously to get your answer. solve for f in terms of s in the first equation. this is already done because the equation states that: f = s + 30 substitute for f in the second equation. second equation is: f + 5 = 3 * (s + 5) equation becomes: s + 30 + 5 = 3 * (s + 5) simplify to get: s + 35 = 3*s + 15 subtract s from both sides of this equation and subtract 15 from both sides of this equation to get: 20 = 2*s divide both sides of this equation by 2 to get: s = 20/2 = 10 from the first equation, we get: f = s + 30 becomes f = 10 + 30 becomes f = 40 we have: f = 40 s = 10 substitute f = 40 and s = 10 in both original equations to see if they are true. f = s + 30 becomes 40 = 10 + 30 becomes 40 = 40 which is true. f + 5 = 3 * (s + 5) becomes 40 + 5 = 3 * (10 + 5) becomes 45 = 30 + 15 becomes 45 = 45 which is also true. both equations are true confirming the values for f and s of 40 and 10 are good.